The chronicles of Downton Abbey - Fellowes, Jessica (St. Martin's Press, 2012)
"The Chronicles of Downton Abbey, carefully pieced together at the heart and hearth of the ancestral home of the Crawleys, takes readers deeper into the story of every important member of the Downton estate.This lavish, entirely new book focuses on each character individually, examining their motivations, their actions, and the inspirations behind them."--